Social norm perception in economic laboratory experiments: inexperienced versus experienced participants - Schmidt, Robert J.; Schwieren, Christiane; Sproten, Alec N. (Discussion paper series, 2018)
We study whether social norm perception in economic laboratory experiments differs between subjects that participate for the first time and subjects that already participated many times. Consistent with previous studies, inexperienced subjects pronounce egalitarianism, while experienced subjects pronounce efficiency and the maximization of their own earnings. Moreover, experienced subjects evaluate exploitation and deception of other individuals in the lab as more appropriate than inexperienced subjects. Field norms also slightly differ between the two groups, but to a lower extent than lab norms. We therefore conclude that learning effects are more important than selection effects for explaining differences between inexperienced and experienced participants. We also conduct exploratory analyses on the relation between lab and field norms and find that behaving unsocial in the lab is considered substantially more appropriate than in the field. This appears inconsistent with the hypothesis that social preferences measured in economic experiments are inflated and indicates a distinction between revealed social preferences and the elicitation of normatively appropriate behavior.
Keywords: Graue Literatur